Economic Cost Prediction Model for Building Construction Based on CNN-DAE Algorithm - Yang, Xueqin (Informatica, 2025)
This paper aims to explore the effectiveness of constructing the construction economic cost prediction model of construction engineering by using CNN-DAE algorithm combined with CNN-DAE. As the construction cost of construction engineering is affected by a variety of complex factors and has high nonlinear and dynamic changes, traditional prediction methods are often difficult to achieve ideal prediction accuracy. Therefore, this paper proposes an innovative predictive model to address these challenges. The final experimental results show that the construction economic cost prediction model based on CNN-DAE algorithm can more accurately capture the change trend of construction cost in terms of prediction accuracy, and provide strong decision support for project managers. In addition, the model has strong generalization ability, and can adapt to different scales and types of construction projects.